Biallelic variants in the NDUFAF6 cause mitochondrial respiratory complex assembly defects associated with Leigh syndrome in probands - Yuwei Zhou; Xiaofei Zeng; Luyi Zhang; Xiaojie Yin; Xue Ma; Keyi Li; Peijing Qiu; Xiaoting Lou; Liqin Jin; Ya Wang; Yanling Yang; Ting Shen (Molecular Genetics and Metabolism Reports)
Background: Variants in NDUFAF6 have been reported to be associated with Leigh syndrome. However, further expansion of the NDUFAF6-phenotype and variants spectrum of NDUFAF6-related Leigh syndrome are still required. Methods: Two patients diagnosed with Leigh syndrome were recruited, and whole-exome sequencing was performed to identify the genetic variants responsible for the abnormal gait, dystonia, and bilateral basal ganglia lesions, followed by validation using Sanger sequencing. Detailed medical records of the patients were collected and reviewed. Patient-derived immortalized B lymphocytes were generalized for functional assays. The clinical manifestations of the patients in this study and previously reported studies are summarized. Results: Two patients developed gait dystonia followed by rapid progression to generalized dystonia and psychomotor regression. Brain magnetic resonance images showed lesions in bilateral symmetric basal ganglia. We identified that patient 1 and patient 2 had two missense changes (NM_152416 c.371 T > C, c.923 T > C and c.371 T > C, c.920 A > T) in NDUFAF6, respectively. The deficiency of mature super complex of complex I was confirmed in patient-derived immortalized B lymphocytes. Meanwhile, cellular ATP production was decreased, and mitochondrial ROS was increased. A literature review of 18 patients carrying variants in NDUFAF6 was conducted, focusing on neurological presentation. Conclusions: NDUFAF6-related Leigh syndrome is a relevant cause of initial symptoms with abnormal gait, dystonia, and bilateral basal ganglia lesions. Two novel genetic variants, c.923 T > C and c.920 A > T were reported, which expands NDUFAF6-related Leigh syndrome and is advantageous for genetic counseling.